The Emotional Intelligence, its importance in the learning process - García Retana, José Ángel (2012)
Within the learning process, cognitive aspects have been privileged over emotional aspects. For some experts, both aspects should be considered separately; however, it might not be suitable if we are to achieve overall development of the learner. In order to accommodate emotional aspects in the educational process, they should be categorized as what they consist on, how they help emotional education to take place and their role as components of the learning process. Additionally, teachers' roles as well as teacher and student emotions should be considered as they affect their own learning processes. Finally, the relationship between emotions and learning styles is to be considered.